Exploring Environmental Responsibility and Justice in Don’t Look Up Movie: A Kerafian Ethical Analysis - Ayiz, Abdul; Jamilah, Ana Shofiana (Universitas Pamulang, 2025)
Amid escalating global environmental crises, environmental images in movies play an indispensable role in shaping public consciousness and attitudes toward ecological challenges. This study investigates the portrayal of environmental ethics in the film Don’t Look Up (2021) through Kerafian ethical analysis. As environmental degradation intensifies, cinematic media emerges as a pivotal force in fostering awareness and influencing public perceptions. A qualitative content analysis was conducted, analyzing key scenes and dialogues to identify and interpret ethical themes in the film, guided by the theoretical constructs from Keraf (2010) to extract and categorize ethical themes. Through the analysis of key scenes and dialogues, the study elucidates how these principles manifest, offering a critique of humanity’s inadequate response to ecological threats. Data were collected through a systematic examination of the film’s narrative, focusing on the integration of core ethical principles, including responsibility, cosmic solidarity, compassion for nature, justice, and democracy (Keraf, 2010). The findings reveal that the film emphasizes collective action, moral accountability, and the urgency of environmental preservation, while simultaneously critiquing political inertia and self-interest. The study underscores the potential of cinematic media to enhance environmental awareness and mobilize public attitudes, positioning Don’t Look Up as a compelling narrative that critiques humanity’s inadequate response to ecological threats